2008
DOI: 10.1080/01494920802013078
|View full text |Cite
|
Sign up to set email alerts
|

Expectations, Aspirations, and Achievement Among Latino Students of Immigrant Families

Abstract: This study examines the relationship between various measures of parental and student expectations and aspirations and math achievement among Latino 12th graders of immigrant parents in the Educational Longitudinal Study (ELS): 2002 database. Findings indicate parental expectations and aspirations were not significant predictors of student achievement after controlling for an index of covariates. Moreover, neither were student expectations, agreement between student and parent expectations, nor student percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
(57 reference statements)
1
17
0
3
Order By: Relevance
“…Analyses conducted with a small sample of 57 found no significant paths from early parental expectations to later school performance (as measured by teacher ratings) or to reading and math test scores. Similar results emerged from a large study of 1,050 Latino immigrant students and families, which found that parental expectations assessed when children were 10th graders were not related to children's math achievement at 12th grade (Carpenter 2008).…”
Section: Evidence Of An Association Between Parental Expectations Andsupporting
confidence: 62%
See 4 more Smart Citations
“…Analyses conducted with a small sample of 57 found no significant paths from early parental expectations to later school performance (as measured by teacher ratings) or to reading and math test scores. Similar results emerged from a large study of 1,050 Latino immigrant students and families, which found that parental expectations assessed when children were 10th graders were not related to children's math achievement at 12th grade (Carpenter 2008).…”
Section: Evidence Of An Association Between Parental Expectations Andsupporting
confidence: 62%
“…This motivational function of parental expectations is supported by eight articles demonstrating a strong association between parental expectations and students' expectations or aspirations (Benner and Mistry 2007;Beutel and Anderson 2008;Carpenter 2008;Hao and Bonstead-Burns 1998;Rutchick et al 2009;Smith-Maddox 2000;Trusty 2002;Trusty et al 2003). A recent longitudinal study of 884 children aged 6 to 13 years when the study began demonstrated the long-lasting effect of parental expectations on children's expectations.…”
Section: High Parental Expectations Indicate That Parents Value Achiementioning
confidence: 76%
See 3 more Smart Citations